Indeterminate form of Chagas disease: historical, conceptual, clinical, and prognostic aspects - Alejandro Marcel Hasslocher-Moreno; Sergio Salles Xavier; Roberto Magalhães Saraiva; Andréa Silvestre de Sousa (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract Chagas disease (CD) remains a serious endemic disease in Latin America and a major public health problem. Because of globalization, the disease has spread to non-endemic areas in the northern hemisphere. In the chronic phase of the disease, most patients present with the indeterminate form (IF), characterized by positive serology for Trypanosoma cruzi, absence of clinical findings, and normal findings in electrocardiogram (ECG). IF was not recognized as a clinical entity until decades after the discovery of the disease, and only in the 1940-50s, it was categorized as a form of CD, and its conceptual definition was ratified in the 1980s. Children, adolescents, and young adults with the IF benefit from etiological treatment and tend to have less progression to heart disease in the long term than the untreated ones. IF patients have an essentially benign clinical condition, and their prognosis can be compared to that of healthy individuals with normal ECG findings. Currently, because of aging, patients with the IF have comorbidities that require attention in health services.